An amperometric biosensor based on Cu2O@Au nanocomposites for the detection of galectin-1 via lactose–galectin interactions. (17th September 2019) - Long, Feng; Li, Wei; Chen, Wanling; Liu, Danni; Chen, Yue; Zhou, Rui; Li, Penghui
Abstract: In this work, a novel label-free electrochemical biosensor is developed for the detection of galectin-1 (Gal-1) based on gold nanoparticle (AuNP) loaded octahedral Cu2 O (Cu2 O@Au) nanocomposites. The AuNPs on the surface of the Cu2 O nanocrystals not only enhance the electrochemical performance, but also serve as the binding sites for the lactose ligand which can specifically bind with Gal-1. The Cu2 O@Au nanocomposites provide the synergic effect of electrochemical signal amplification and lactose–galectin reaction as the recognition strategy. Under optimal conditions, the proposed biosensor exhibits a variation of electrochemical responses to different concentrations of Gal-1 ranging from 0.1 pg ml −1 to 10 ng ml −1 . This work presents an alternative electrochemical biosensor for the detection of tumor biomarkers based on a simple and economical lactose ligand incorporated Cu2 O@Au biosensor platform.